Assessing Occupational Hazards for Pre-Construction Works at Construction Site - Shandren Nair Mathavan; Syahrun Neizam Mohd Dzulkifli; Amin Ab Hamid (Progress in Engineering Application and Technology, 2026)
The construction industry is one of the high-risk work environments, especially during the pre-construction phase due to the various dynamic activities along with the presence of heavy equipment, excavation and piling works. Despite the already existing safety regulations, construction site accidents remain as a serious problem in early phases of construction. This study aims to assess occupational hazards associated with pre-construction works at a construction site. These early-stage operations often involve high levels of risk to workers’ safety and health, especially when proper safety controls are not effectively implemented. The study applied the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach to systematically identify, evaluate, and manage workplace hazards. Data were collected through site observations (GEMBA walk), focused group discussions, and document analysis, including incident reports and company safety manuals. The findings were able to identify various types of hazards, including physical, chemical, ergonomic, and psychosocial risks encountered during pre-construction activities. A risk assessment was conducted using a risk matrix to determine the likelihood and severity of each hazard. Control measures were proposed based on the hierarchy of controls, such as elimination, substitution, engineering controls, administrative controls, and personal protective equipment. This study contributed to improved safety practices in the construction industry and serve as a useful reference for site management and future researchers.